Relevance of Knowledge Sharing to Knowledge Retention and Growth: An Overview - Okite, Onyedikachi Maxwell; Owali, Joseph Orji; Adigbo, Oluchi Jovita; Olughu, Iro Imaga (The Melting Pot, 2019)
The paper relies on existing literature in knowledge and knowledge management. Knowledge sharing is conceptualized as the distribution, dissemination, transfer and exchange of knowledge, experience and ideas within and among individuals or groups in organizations with the aim of making such knowledge, experience and ideas available for application in finding solutions to specific organizational problems and challenges. Types and characteristics of knowledge are highlighted; mechanisms and tools for knowledge sharing are explained. The paper recommends that knowledge sharing activities should be sponsored and supported by individuals and groups, government agencies and governments at all levels for knowledge retention, knowledge growth and knowledge expansion, for the overall social and economic well-being of the society at large.